Antioxidant and Anti-tyrosinase Activities of Phenolic Extracts from Rape Bee Pollen and Inhibitory Melanogenesis by cAMP/MITF/TYR Pathway in B16 Mouse Melanoma Cells - Sun, Liping; Guo, Yan; Zhang, Yanxin; Zhuang, Yongliang (Frontiers in Pharmacology, 2017)
Rape bee pollen possesses many nutritional and therapeutic properties because of its abundant nutrimental and bioactive components. In this study, free (FPE) and bound (BPE) phenolic extracts of rape bee pollen were obtained, phenolic and flavonoid contents were determined, and composition of phenolic acids was analyzed. In vitro antioxidant and anti-tyrosinase (TYR) activities of FPE and BPE were compared, and inhibitory melanogenesis of FPE was further evaluated. Results showed FPE and BPE contain total phenolic contents of 11.76 and 0.81 mg gallic acid equivalents/g dry weight (DW) and total flavonoid contents of 19.24 and 3.65 mg rutin equivalents/g DW, respectively. Phenolic profiling showed FPE and BPE fractions contained 12 and 9 phenolic acids, respectively. FPE contained the highest rutin content of 774.87 μg/g. FPE and BPE showed the high antioxidant properties in vitro and high inhibitory activities for mushroom TYR. Higher activities of FPE than those of BPE can be attributed to difference in their phenolic compositions. Inhibitory melanogenesis activities of FPE against B16 were further evaluated. Results showed suppressed intracellular TYR activity, reduced melanin content, and promoted glutathione synthesis (p<0.05) in FPE-treated cells. FPE reduced mRNA expression of TYR, TYR-related protein (TRP)-1 and TRP-2, and significantly suppressed cyclic adenosine monophosphate (cAMP) levels through down-regulation of melanocortin 1 receptor gene expression (p<0.05). FPE reduced mRNA expression of microphthalmia-associated transcription factor (MITF), significantly inhibiting intracellular melanin synthesis (p< 0.05). Hence, FPE regulates melanogenesis of B16 cells involved in cAMP/MITF/TYR pathway. These results revealed that FPE can be used as pharmaceutical agents and cosmetics to protect cells from abnormal melanogenesis.